The hydrogenation of calix[4]pyrroles leading to the novel ligand system calix[4]pyrrolidine: Their properties and their application - (:unkn) unknown (My University, 2025)
"Let's get practical". With these words George Whitesides and John Deutch are launching an appeal to to rethink the future of chemistry in the 21st century (Nature, 2011, Vol. 469, p. 21-22). To solve the challenges of the 21th century chemistry will have to concentrate on solving problems of importance to our societies. Our group is concentrating on the bio-inspired approach to novel macrocyclic ligand systems. The prototypical metal complexes of natural macrocycles fullfill vital tasks, such as photochemical energy production, energy storage through redox processes and the transport and use of oxygen. The simple and efficient synthesis of calix[4]pyrrole has been known for more than 125 years. The connectivity of these heterocyclic calix[4]arenes is identical with the skeleton of the "pigments of life". Despite this ressemblence of the connectivity graph, the chemical properties of the porphyrin derived natural "pigments of life" and the synthetic calix[4]pyrroles are completely different. The "pigments of life" are almost ideal ligands and form metal complexes with great ease. The function of the indivudual "pigment of life" depends on the metal but also in a subtle way on the ligand and finally on the second coordination sphere. The goal of our research project is to make use of the efficient access to the calix[4]pyrrole skeleton and to transform these compounds into excellent ligands by a "simple" hydrogenation step. We have reported proof-of-principle results by isolating and characterizing the totally reduced calix[4]pyrrolidine. The great challenge is to make the access to this novel macrocyclic structure efficient and experimentally easy.
Keywords: Calix[4]pyrrole; Macrocyclic Ligands; Pyrrole; Stereochemistry; Hydrogenation; Heterogenous; Organocatalysis